Fulminant Guillain-Barré syndrome in a patient with systemic lupus erythematosus. Issue 1 (14th January 2019) - Coomes, Eric Anthony; Haghbayan, Hourmazd; Spring, Jenna; Mehta, Sangeeta
Abstract : A 45-year-old man with a history of systemic lupus erythematosus presented with progressive weakness and areflexia. Electromyogram revealed reduced motor and sensory amplitudes without demyelinating features. He was clinically diagnosed with the acute motor and sensory axonal neuropathy variant of Guillain-Barré syndrome. Despite intravenous immunoglobulin therapy, he deteriorated with loss of all voluntary motor function and cranial nerve reflexes. Concomitant investigations revealed class V lupus nephritis. Therapy was initiated with plasma exchange, glucocorticoids and further immunosuppression, with gradual neurological recovery. We present the first documented case of fulminant Guillain-Barré syndrome as a neuropsychiatric manifestation of systemic lupus erythematosus, highlighting how immune-mediated polyneuropathy via diffuse deafferentation may mimic the outward appearance of brain death. While glucocorticoids are not indicated in idiopathic Guillain-Barré, when this neurological disorder is a consequence of systemic lupus erythematosus, immunomodulatory treatment should be initiated to prevent neurological deterioration.